The Impact of Laboratory Automation and AI on Healthcare Delivery: A Systematic Review - Hadi Khwaji, Ahmed; Ahmed Daghriri, Mustafa; mohmmed awaji , Faisal ali (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2024)
Laboratory automation and artificial intelligence (AI) are transforming healthcare delivery by improving diagnostic accuracy, efficiency, and patient outcomes. This systematic review examines the current impact of laboratory automation and AI on healthcare services, focusing on diagnostic accuracy, turnaround times, operational efficiency, and patient care. A comprehensive search of studies from 2016 onwards identified significant advancements in laboratory processes due to automation and AI, resulting in faster, more reliable test results and streamlined workflows. Key findings highlight that automated technologies reduce human error, enhance diagnostic precision, and optimize resource allocation, leading to cost savings and improved patient satisfaction. Despite the promising benefits, challenges such as high implementation costs, integration issues, and ethical concerns related to data privacy remain barriers to widespread adoption. This review concludes that while laboratory automation and AI have shown considerable potential to enhance healthcare delivery, further research is needed to address existing limitations and ensure equitable access. Future trends indicate that continued development in AI algorithms, predictive analytics, and big data integration will further revolutionize laboratory medicine and improve healthcare delivery worldwide.